METHODS OF BENEFICIATION OF POTASH ORES AND POTASH MINES - Niyozov Sobir Ahror o‘g‘li; Maxmudov Rafiq Amonovich; Baxshilloyev Nozim Komil o‘g‘li (Journal Park Publishing, 2022)
Studies were conducted on the development of the technology of flotation concentration of potassium ores: sylvinite, kainite-halite, carnallite-kainite-halite. Optimum flotation conditions are developed for each ore: salt content, density and pH level of the dispersion medium, collector of the useful component, auxiliary reagents - blowing agents, dewatering agents, depressants, to obtain a high enriched potassium concentration. The density of 1235 kg/m provides amines. Kainite-halite ore is beneficiated by direct flotation in an aqueous saturated solution of magnesium chloride with a density of 1284 kg/m3 and a pH of 6–7. In beneficiation of carnallite-kainite-halite ore, beneficiation is carried out by reverse flotation in aqueous solutions of magnesium chloride with a density of 1285–1295 kg/m3 and a pH of 3–4, using alkylmorpholine hydrochloride salt as a halite collector.
Keywords: salt composition, density and pH of the dispersion medium, potassium chloride, Halite flotation of 5 g/t ore